Bioinformatic analysis of short-chain dehydrogenase/reductase proteins in plant peroxisomes - Zhang, Yuchan; Wang, Xiaowen; Wang, Xinyu; Wang, Yukang; Liu, Jun; Wang, Saisai; Li, Weiran; Jin, Yijun; Akhter, Delara; Chen, Jiarong; Hu, Jianping; Pan, Ronghui (Frontiers in Plant Science, 2023)
Peroxisomes are ubiquitous eukaryotic organelles housing not only many important oxidative metabolic reactions, but also some reductive reactions that are less known. Members of the short-chain dehydrogenase/reductase (SDR) superfamily, which are NAD(P)(H)-dependent oxidoreductases, play important roles in plant peroxisomes, including the conversion of indole-3-butyric acid (IBA) to indole-3-acetic acid (IAA), auxiliary β-oxidation of fatty acids, and benzaldehyde production. To further explore the function of this family of proteins in the plant peroxisome, we performed an in silico search for peroxisomal SDR proteins from Arabidopsis based on the presence of peroxisome targeting signal peptides. A total of 11 proteins were discovered, among which four were experimentally confirmed to be peroxisomal in this study. Phylogenetic analyses showed the presence of peroxisomal SDR proteins in diverse plant species, indicating the functional conservation of this protein family in peroxisomal metabolism. Knowledge about the known peroxisomal SDRs from other species also allowed us to predict the function of plant SDR proteins within the same subgroup. Furthermore, in silico gene expression profiling revealed strong expression of most SDR genes in floral tissues and during seed germination, suggesting their involvement in reproduction and seed development. Finally, we explored the function of SDRj, a member of a novel subgroup of peroxisomal SDR proteins, by generating and analyzing CRISPR/Cas mutant lines. This work provides a foundation for future research on the biological activities of peroxisomal SDRs to fully understand the redox control of peroxisome functions.